Penerapan Model Pembelajaran Teams Games Tournament (Tgt) Berbantuan Flash Card Dalam Meningkatkan Kemampuan Membaca Siswa Kelas Iv Sekolah Dasar - Ni Kadek Rini Yanti; Ni Wayan Sri Darmayanti; I Nengah Sueca (Jurnal Pendidikan Rafflesia, 2026)
Reading ability is one of the essential competencies that elementary school students must master because it supports learning success across various subjects. However, preliminary observations conducted in the fourth grade of SD Negeri 1 Susut indicated that students' reading ability was still relatively low. Many students experienced difficulties in comprehending reading texts, identifying important information, determining the main idea, and retelling the content of a text in their own words. This study aimed to describe the implementation of the Teams Games Tournament (TGT) learning model assisted by flash card media and to determine the improvement in students' reading ability after the implementation of the model. This research employed Classroom Action Research (CAR) consisting of two cycles, namely planning, action, observation, and reflection. The subjects of the study were 23 fourth-grade students of SD Negeri 1 Susut. Data were collected through reading tests and documentation and analyzed using descriptive quantitative analysis by calculating the mean score and the percentage of learning mastery. The results showed a significant improvement in students' reading ability. The average score increased from 68.04 in the initial condition to 82.39 in Cycle I and further improved to 88.70 in Cycle II. Classical learning mastery also increased from 30.43% in the initial condition to 69.57% in Cycle I and reached 86.96% in Cycle II. In addition to improving reading achievement, the implementation of the TGT learning model assisted by flash cards also enhanced students' participation, cooperation, learning motivation, and self-confidence during the learning process. Therefore, the Teams Games Tournament (TGT) learning model assisted by flash cards is effective in improving the reading ability of fourth-grade elementary school students.